Interlayer vibrational modes in few-quintuple-layer Bi2Te3 and Bi2Se3 two-dimensional crystals : raman spectroscopy and first-principles studies - Luo, Xin (2015)
Layered materials, such as graphite/graphene, boron nitride, transition metal dichalcogenides, represent materials in which reduced size, dimensionality, and symmetry play critical roles in their physical properties. Here, we report on a comprehensive investigation of the phonon properties in the topological insulator Bi2Te3 and Bi2Se3 two-dimensional (2D) crystals, with the combination of Raman spectroscopy, first-principles calculations, and group theory analysis. Low frequency (<30cm−1) interlayer vibrational modes are revealed in few-quintuple-layer (QL) Bi2Te3/Bi2Se3 2D crystals, which are absent in the bulk crystal as a result of different symmetries. The experimentally observed interlayer shear and breathing mode frequencies both show blueshifts, with decreasing thickness in few-QL Bi2Te3 (down to 2QL) and Bi2Se3 (down to 1QL), in agreement with first-principles calculations and a linear chain model, from which the interlayer coupling force constants can be estimated. Besides, an intense ultralow (<12cm−1) frequency peak is observed in 2–4QL Bi2Te3, which is tentatively attributed to a substrate-induced interface mode supported by a linear chain model analysis. The high frequency Raman peaks exhibit frequency shifts and broadening from 3D to 2D as a result of the phonon confinement effect. Our studies shed light on a general understanding of the influence of dimensionality and crystal symmetry on the phonon properties in layered materials.